POLYMORPHISM OF THE GENES OF ESTROGEN-METABOLISING ENZYMES IN PATIENTS WITH ENDOMETRIOSIS - Константин Сергеевич Кублинский; Ольга Ивановна Уразова; Вячеслав Викторович Новицкий; Ирина Георгиевна Куценко (The Publishing House Medicine and Enlightenment, 2017)
Subject - polymorphism of genes of estrogen-metabolising enzymes in patients with endometriosis. Objective - to perform analysis of relationship among allelic variants of genes of oestrogen-metabolising enzymes and development of external genital endometriosis (EGE), variants of its clinical progression and multiple-modality treatment efficacy. Methods. Laparoscopy was performed for 417 women with EGE (treatment group) and 112 women without EGE (control group). After laparoscopically verified diagnosis for 358 women from both groups (251 with EGE and 107 without EGE) there were regions of polymorphic genes of estrogen-metabolising enzymes A-4889G CYP1A1, С-734А CYP1A2, G-638А SULT1A1 and С-174T SULT1E1 identified in RFLP-analysis. Main results. It has been established that carriage of not only separate polymorphic genes of estrogen-metabolising enzymes CYP1A1 A-4889G (Allele G and Genotypes GG, АG) and CYP1A2 С-734А (Allele А and Genotypes СА, АА), but also their combinations predisposes to EGE development in women of reproductive age. Carriage of Genotype СA of polymorphism С-734А of CYP1A2 gene predisposes to development of pelvic pains during EGE. The most potent combination of polymorphisms of genes of estrogen-metabolising enzymes which predisposes to EGE development is CYP1A1АА/CYP1A2СА/SULT1A1GG/SULT1E1CC combination, while CYP1A1АА/CYP1A2СС/SULT1A1GА/SULT1E1CC combination predisposes to formation of I-II stages of EGE distribution, as well as CYP1A1АА/CYP1A2СА/SULT1A1GG/SULT1E1CC combination predisposes to development of endometriosis-associated infertility, while CYP1A1АG/CYP1A2CC/SULT1A1GA/SULT1E1CC combination predisposes to efficient treatment of infertility during EGE. Scope of application. The obtained results will allow to form risk groups of EGE development with the purpose of its primary prevention and efficient treatment of endometriosis-associated infertility. Conclusions. Polymorphic variants of estrogen-metabolising enzymes A-4889G CYP1A1, С-734А CYP1A2, G-638А SULT1A1 and С-174T SULT1E1 (separately or in combinations) predispose to EGE development, and are associated with its clinical evidence, distribution stage and treatment efficacy.